The Influence of Interpersonal Skills, Salesmanship Skills, and Work Environment on Medical Representative Performance - Saragih, Elvira Inggrid Rodearni; Simanjorang, Elida Florentina Sinaga; Zebua, Yuniman (Almana : Jurnal Manajemen dan Bisnis, 2023)
Interpersonal skills, salesmanship skills, and work environment are some of the factors that influence employee performance. For pharmaceutical companies, the performance of the Medical Representative (MR) is a very important factor for the company in achieving its business goals. Therefore, pharmaceutical companies must ensure that their MRs have good interpersonal skills to be able to establish good relationships with other medical professionals, effective salesmanship skills to market pharmaceutical products, and a conducive work environment to motivate MRs to work. This study aims to describe and test how much influence partially and simultaneously the interpersonal skills, salesmanship skills, and work environment variables have on the performance of the Asahan Labuhanbatu medical representative area, as well as being an input for pharmaceutical companies on how to improve the performance of Medical Representative employees. This type of research is a quantitative descriptive study with a total of 30 respondents. The results of the research show that both partially and simultaneously, the interpersonal skills, salesman skills, and work environment variables have a positive and significant effect on the performance of the Medical Representative Area Asahan - Labuhanbatu.